2020
DOI: 10.1155/2020/1215395
|View full text |Cite
|
Sign up to set email alerts
|

Green-Synthesized Silver Nanoparticles Induced Apoptotic Cell Death in MCF-7 Breast Cancer Cells by Generating Reactive Oxygen Species and Activating Caspase 3 and 9 Enzyme Activities

Abstract: Silver nanoparticles are among the most significant diagnostic and therapeutic agents in the field of nanomedicines. In the current study, the green chemistry approach was made to optimize a cost-effective synthesis protocol for silver nanoparticles from the aqueous extract of the important anticancer plant Fagonia indica. We investigated the anticancer potential and possible involvement of AgNPs in apoptosis. The biosynthesized AgNPs are stable (zeta potential, -16.3 mV) and spherical with a crystal size rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 84 publications
(79 reference statements)
4
48
0
Order By: Relevance
“…AgNPs generate different biochemical pathways, including ROS-mediated mitochondrial dysfunction, DNA damage, and apoptosis, that are related to the enhanced anticancer activities in MCF-7 cells. 53 , 59 The results we obtained in this study are in line with the findings of researchers in previous examinations. Mugade et al bioengineered (mannan sulfate-capped AgNPs) to downregulate TNF-α and IL-6 expression in rats.…”
Section: Discussionsupporting
confidence: 93%
“…AgNPs generate different biochemical pathways, including ROS-mediated mitochondrial dysfunction, DNA damage, and apoptosis, that are related to the enhanced anticancer activities in MCF-7 cells. 53 , 59 The results we obtained in this study are in line with the findings of researchers in previous examinations. Mugade et al bioengineered (mannan sulfate-capped AgNPs) to downregulate TNF-α and IL-6 expression in rats.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mechanism through which ZnO-NP is capable of conferring partly differential responses remains controversial. A majority of researchers believe that differential physicochemical characteristics of nanoparticles relative to the bulk contributed to differences in their uptake kinetics, subsequent interactions with biomolecules, signaling, and responses [1][2][3][10][11][12]22,27,28]. More studies are, therefore, required to confirm this hypothesis.…”
Section: Plos Onementioning
confidence: 99%
“…Nowadays, nanotechnology provides great opportunities for development in a plethora of disciplines, including biotechnology and agriculture [1][2][3]. Taking account of agriculture's requirements, attempts have been made to enhance crop productivity and fruit quality, to improve immunity, and to reduce the consumption of chemical fertilizers/pesticides [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) produced in normal cells and have roles in many physiological conditions [21]. Under excessiveness of ROS, a series of cellular events were occurring results in lipid peroxidation, DNA damaging, cell cycle arrest, and promote apoptosis pathway [22]. It has been reported that new strategies for targeting ROS contribute to the cancer therapy [23].…”
Section: Measurement Of Reactive Oxygen Species Productionmentioning
confidence: 99%
“…In the current study, we evaluated the roles of pro-apoptotic Bax and CAD regulation in relation to the apoptotic death of cancer cells [22]. The mRNA expression levels of genes in AgNPs-OAL -mediated apoptotic cells were displayed by qRT-PCR method, which is presented in Fig.…”
Section: Agnps-oal Induce Apoptosis In Mda-mb231 Cellsmentioning
confidence: 99%